PENYEDIAAN SUMBER DAYA LISTRIK BERBASIS SOLAR SEL DI GEREJA GPDI BUKIT HERMON TO’ LIMBONG LEMBANG TONDON, KECAMATAN TONDON, KABUPATEN TORAJA UTARA - Patabang, Simon (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Without electrical energy, electronic equipment cannot be used as a work aid to meet human needs. The GPDI Church of the Bukit Hermon To' Limbong Congregation, is one of the houses of worship whose location is not yet reached by the PLN electricity network. To get electrical energy, it still takes a long time because they are waiting for the plan to add electricity to the church site. The church already has several electronic devices such as sound systems and pianos that were donated by the congregation. However, these tools cannot be used because electrical energy is not yet available in the church. To meet the electricity needs in the church, solar cell-based electrical energy is provided. Service activities are carried out using the method of applying solar cell technology by installing solar panels. The function of the solar panel is to convert solar energy into direct current electrical energy which is then converted into alternating current electrical energy. With the installation of a 160 Wp solar panel, the electricity source is already available, in the Bukit Hermon GPDI church so that the electric lighting in the church is lit during the day and at night. Electronic devices that have not been used before, can already be functioned properly when carrying out activities